Education and the Conflict Perspective: A College Admissions Committee Activity - Ferguson, Todd; Andercheck, Brita; McClure, Paul (TRAILS: Teaching Resources and Innovations Library for Sociology, 2015)
This in-class activity is designed to illustrate the conflict perspective and to further a student’s understanding of how the education system perpetuates economic, gender and social class inequalities. In this activity, students take on the role of a college admissions committee member and assess potential candidates for admission in small groups. As small groups decide on whom they will admit, the instructor gives updates that change the admission process’ dynamics. As the updates come in, students will be challenged to address the real life constraints and wrestle with which candidate to admit. This activity engages the entire classroom and requires students to interact directly with their classmates in their discussion of education system and the conflict perspective.